2011
DOI: 10.1002/uog.9626
|View full text |Cite
|
Sign up to set email alerts
|

P01.12: Reference ranges of fetal length and area of corpus callosum by three‐dimensional ultrasonography

Abstract: with abnormal measurements of the fourth ventricle (intracranial translucency -IT) that provided the morphological support to evaluate the efficiency and specificity of posterior brain parameters. Prospectively we evaluated mean values and repeatability of most efficient and specific considered parameters of the posterior brain complex -brain stem diameter (BS), brain stem to occipital bone distance (BSOB) and BS to BSOB ratio were performed in 112 fetuses in 2D before obtaining 3D volumes, used to measure the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…However, they did not provide reference ranges for the cavum septi pellucidi. In a preliminary study performed previously by our group, which evaluated 70 pregnant women between 20 and 33 weeks, the mean corpus callosum length ranged from 21.7 to 38.7 mm 13 . The results of this study are very similar to those observed in the previous study but with more power.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, they did not provide reference ranges for the cavum septi pellucidi. In a preliminary study performed previously by our group, which evaluated 70 pregnant women between 20 and 33 weeks, the mean corpus callosum length ranged from 21.7 to 38.7 mm 13 . The results of this study are very similar to those observed in the previous study but with more power.…”
Section: Discussionsupporting
confidence: 88%
“…All patients agreed to voluntarily participate in the study. Seventy patients were evaluated in our previous study, 13 which showed a strong correlation between corpus callosum measurements and gestational age, motivating our group to continue the study.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 32 papers, 6 were excluded from further review. The remaining 26 articles [4][5][6][7][8][9][10][11][12][13]15,17,18,[20][21][22]24,25,27,30,31,33,44,45 were reviewed qualitatively (Tables 1 and 2) and of these, 10 were included for quantitative review. 4,5,7,9,12,15,21,24,30,33 We contacted the corresponding author of all of the articles excluded for quantitative review due to the way in which the data were reported (eg, only graphically or not reported by gestational age); however, only one author sent us data suitable for analysis.…”
Section: Eligibility Criteria and Study Selectionmentioning
confidence: 99%
“…A large number of published nomograms exist for both CSP and CC biometry on prenatal ultrasound 4–33 . However, many of these studies have small sample sizes, unclear measurement techniques, or unconventional reporting standards.…”
mentioning
confidence: 99%
“…3). Visentainer et al (2010) established reference ranges for corpus callosum length and area in fetuses between 20 and 33 wk of gestation using 3-DUS. These authors reported that mean corpus callosum length increased from 21.7 to 38.7 mm between 20 and 33 wk of gestation and that mean corpus callosum area increased from 55.2 to 142.2 mm 2 between 20 and 33 wk of gestation.…”
Section: -D Ultrasound and The Study Of Fetal Brain Anatomy: ''The Nmentioning
confidence: 99%